(untitled) (Res Medica, 2015)
Introduction: Recent research has highlighted the need to improve communication with mechanically ventilated patients. There are a number of studies currently evaluating the usefulness of augmentative and alternativen communication methods (AACs), but a significant gap still exists in understanding patients’ key needs during the ventilation period. Aims: 1) To determine the perceptions of patients and healthcare staff on the use of AACs. 2) To find out patients’ key needs during ventilator treatment, within the context of Ward 118 in the Royal Infirmary of Edinburgh. 3) To use the results of this study to propose larger scale research into adapting a specific electronic device (Predictable) to aid communication. Methods: This qualitative study adopted semi-structured interviews lasting 10–20 minutes with 13 patients and 18 members of healthcare staff and applied thematic analysis in interpreting interview findings. Results: There was a mismatch between patient and staff perceptions on the usefulness of closed yes/no questions and lip reading. Aided AACs, such as picture boards, pen and paper, and sketch boards are also underused. Most patients and staff used a combination of methods rather than any one method alone. This study also found that patients’ key needs include addressing discomfort related to the ventilator, bed or breathing, emotional needs, trust building with healthcare staff and the need for more information. Conclusion: This study highlights the need for personalized, patient-centred care to facilitate effective communication with ventilated patients.